Variability of Physico-chemical Wood Properties of Khair (Acacia catechu Willd., Provenances - Sharma, Kulwant Rai; Lekha, Chander (Indian Forester, 2012)
Twenty best performing provenances were selected to Investigate the variability In physico-chemical properties of sapwood and heartwood of Acacia catechu. The genotypic correlation was found to be higher than phenotypic and environmental correlation. The sapwood percentage was significantly and negatively correlated with all the parameters except holocellulose content at genotypic and phenotypic level. The significant and positive genotypic, phenotypic correlation coefficients were noticed between specific gravity and wood extractives, specific gravity and lignin content, lignin and extractives. The holocellulose content was significantly and negatively correlated with all the physico-chemical parameters studied In sapwood. The highly significant positive genotyplc correlation coefficient was found between lignin content and cold water solubility (0.989), lignin and hot water and alcohol benzene solubility, specific gravity and cold water solubility, In heartwood. Katha content and cutch content was significantly and positively correlated with moisture content in heartwood and katha content was significantly and negatively correlated with lignin content. The values 01 the heritability factor were high for holocellulose (0.981), lignin (0.944), and specific gravity (0.870). The genetic advance, genetic gain, phenotypic and genotypic coefficient of variation ranged from 0.05-24.31, 2.84-42.81, 1.39-20.77,1.33-20.77, respectively for various parameters In sapwood. The maximum heritability value 0.930 (93.0%) was found in katha content and minimum value of 0.051 (5.10%) was noticed In lignin content In heartwood.